ANALISIS PENYELESAIAN KREDIT BERMASALAH PADA PD. BPR SARIMADU CABANG PEKANBARU - Rini Saputri; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Provision of credit facilities are always followed by various types of risk. Credit risk of the most common is the inability of the debtor to pay back its obligations in the form of loan principal and interest loans, causing a credit crunch. Problem loans are loans that must be resolved and addressed to avoid losses at the bank. PD. BPR Sarimadu Pekanbaru branch is one of the banking institutions which cannot be separated from non-performing loans, requiring the completion of the loans that experienced these problem. The purpose of this study was to determine and analyze the settlement of non-performing loans in the PD. BPR Sarimadu Pekanbaru branch. The sampling technique used is ti assign an informant within the settlement of non-performing loans. As for the informants in this study were employees of credit PD. BPR Sarimadu Pekanbaru branch and debtors. His or of this study showed that the percentage of non-performing loans in 2011-2014 fluctuated and tended to increase. The resolution of troubled debt PD. BPR Sarimadu Pekanbaru branch in the form of credit restructuritation including the rescheduling, restructuring and foreclosure of collateral.Key words: credit risk, non-performing loans, troubled debt setlement